A Daily 1‐km Resolution Greenland Rainfall Climatology (1958–2020) From Statistical Downscaling of a Regional Atmospheric Climate Model. Issue 17 (2nd September 2022) - Huai, Baojuan; van den Broeke, Michiel R.; Reijmer, Carleen H.; Noël, Brice
Abstract: A daily, gridded 1‐km rainfall climatology (1958–2020) for Greenland is presented, including the Greenland ice sheet (GrIS), the peripheral glaciers and ice caps (GIC), and ice‐free tundra. It is obtained by statistically downscaling the 5.5 km output of the regional atmospheric climate model version 2 to a resolution of 1 km, using the elevation dependence of snowfall fraction. Based on this new product, the average total annual rainfall in Greenland during 1958–2020 is estimated to be 111.4 ± 11.2 Gt/year, of which 28.6 ± 6.1 Gt/year falls on the GrIS, 11.4 ± 1.4 Gt/year on the GIC, and 71.4 ± 9.0 Gt/year on the tundra. The downscaled 1 km product better resolves especially the relatively small GIC, more than doubling (+124%) their rainfall compared to the 5.5 km product. The relatively warm southern regions of Greenland have the highest rainfall amounts, with annual values locally exceeding 1, 000 mm. We confirm a significant positive trend in Greenland rainfall (>40 mm/decade), notably in the northwest and mainly due to an increase in rainfall fraction (>3.5%/decade) during July and August. For the whole of Greenland, during 1991–2020 the seasonal rainfall peak has shifted from July to August, with significant increases in September, which receives more rain than June. An analysis of rainfall fraction and near‐surface temperature shows that local warming rates are a good predictor of recent rainfall changes. Key Points: The downscaled daily, gridded 1 km RACMO2.3p2 rainfall product better resolves especially the relatively small peripheral glaciers and ice caps, more than doubling their rainfall compared to the native 5.5 km product A significant positive trend is found in northwest Greenland rainfall, mainly attributable to an increase in rainfall fraction during July and August High correlations between rainfall fraction and near‐surface temperature shows that local warming rates are a good predictor of recent Greenland rainfall changes